2022
DOI: 10.1101/lm.053507.121
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II differentially affects hippocampal glial inflammatory markers in young adult male and female mice

Abstract: Hypertension is a risk factor for neurodegenerative disorders involving inflammation and inflammatory cytokine-producing brain cells (microglia and astrocytes) in the hippocampus and medial prefrontal cortex (mPFC). Here we investigated the effect of slow-pressor angiotensin II (AngII) on gliosis in the hippocampus and mPFC of young adult (2-mo-old) male and female mice. In males, AngII induced hypertension, and this resulted in an increase in the density of the astrocyte marker glial fibrillary acidic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
1
0
0
Order By: Relevance
“…The density of the astrocytic marker GFAP was examined in CA1, CA3, DG and subicular subregions within rostral and caudal hippocampus (Figures 3A,B) of oil and VCD-treated SWDI and WT mice. Consistent with our prior studies in female mouse brain (Milner et al, 2022), GFAP-labeled cells were found throughout the CA1, CA3 and DG (Figure 3). Representative micrographs of GFAP-labeling are shown for rostral CA1 (Figures 3C-F), caudal CA1/subiculum (Figures 3H-K) and the dentate gyrus (Figures 3M,N).…”
Section: Peri-aof Is Associated With Increased Levels Of Reactive Ast...supporting
confidence: 92%
“…The density of the astrocytic marker GFAP was examined in CA1, CA3, DG and subicular subregions within rostral and caudal hippocampus (Figures 3A,B) of oil and VCD-treated SWDI and WT mice. Consistent with our prior studies in female mouse brain (Milner et al, 2022), GFAP-labeled cells were found throughout the CA1, CA3 and DG (Figure 3). Representative micrographs of GFAP-labeling are shown for rostral CA1 (Figures 3C-F), caudal CA1/subiculum (Figures 3H-K) and the dentate gyrus (Figures 3M,N).…”
Section: Peri-aof Is Associated With Increased Levels Of Reactive Ast...supporting
confidence: 92%